1997
DOI: 10.1212/wnl.49.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Interscanner variation in brain MRI lesion load measurements in MS: Implications for clinical trials

Abstract: We evaluated the effect of interscanner variation on brain MRI-measured lesion volumes and measurement reproducibility in MS. Twenty clinically definite MS patients were each scanned on two or three scanners (a total of 14 scanners were used). In addition, a formalin-fixed MS brain was studied on eight scanners from different manufacturers and with different field strengths. For the formalin-fixed MS brain, on each machine we obtained two scans with slice thicknesses of 5 and 3 mm. Only 5-mm-thick slices were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 13 publications
2
40
0
1
Order By: Relevance
“…75,76 Interscanner agreement for quantitative assessments of FLAIR lesion volumes, using quantitative semiautomated thresholding techniques similar to those employed in our study, was 96.7% (95% CI, 95-97.5) for scanners operating at 1.5T field strength and 91.1% (95% CI, 90.2-94.1) for scanners of different field strengths. 77 The effect of such variances on cross-sectional studies such as the one presented here is likely to be small. Every effort was made to assure unbiased measurements; however, lesion thresholds were set manually to detect the subtlest lesion present; thus, there is some subjective interpretations inherent in the thresholding method used for quantification.…”
Section: Study Limitationsmentioning
confidence: 87%
“…75,76 Interscanner agreement for quantitative assessments of FLAIR lesion volumes, using quantitative semiautomated thresholding techniques similar to those employed in our study, was 96.7% (95% CI, 95-97.5) for scanners operating at 1.5T field strength and 91.1% (95% CI, 90.2-94.1) for scanners of different field strengths. 77 The effect of such variances on cross-sectional studies such as the one presented here is likely to be small. Every effort was made to assure unbiased measurements; however, lesion thresholds were set manually to detect the subtlest lesion present; thus, there is some subjective interpretations inherent in the thresholding method used for quantification.…”
Section: Study Limitationsmentioning
confidence: 87%
“…Although there was a change in scanner and slice thickness during the study, this had little influence 40,41 on the large increases seen in the lesion volumes, which included an increase in the median volume by a factor of 11 over a 14-year period. Furthermore, none of these patients were treated with disease-modifying drugs during the first 10 years; three patients received interferon beta after year 10.…”
Section: Discussionmentioning
confidence: 98%
“…Two studies showed significantly higher lesion load measurements at 1.5 T when compared to lower field strengths especially in the infratentorial region [21,22], however, without any implications on this diagnosis of MS according to the Poser criteria [24]. These results could not be confirmed by the following study including a larger cohort of 132 patients with suspected or definite MS [23].…”
Section: Conventional High Field Mri At 3 T In Multiple Sclerosismentioning
confidence: 78%
“…The first studies comparing magnetic field strengths of 0.5 and 1.5 T can be considered as inconclusive [21][22][23]. Two studies showed significantly higher lesion load measurements at 1.5 T when compared to lower field strengths especially in the infratentorial region [21,22], however, without any implications on this diagnosis of MS according to the Poser criteria [24].…”
Section: Conventional High Field Mri At 3 T In Multiple Sclerosismentioning
confidence: 99%